The Processing Technique of Urutan Celeng as A Superior Product for Culinary Tour in Sangeh Abiansemal Tourism Village, Badung, Bali, Indonesia - Sutaguna, I Nyoman Tri; Sirna, I Ketut; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2020)
one of the goals of tourism development in Indonesia is to develop local food in an area including traditional Balinese food globally. For now, this goal has not been achieved as expected. This happens because the local food in the villages is still abundant and not fully utilized. One example is the food that is usually used as a presentation/offering in Sangeh Tourism Village. This research will discuss the types of “Urutan Celeng” that can be developed into superior culinary tourism products as well as what cooking techniques can be done to improve the quality of “Urutan Celeng” in Sangeh Tourism Village, Abiansemal District, Badung Regency. The research method was carried out with a qualitative approach using several The informants were selected purposely and the data collection techniques were carried out by the method of observation, in-depth interviews and documentation studies with the theory developed in the form of the theory of culinary tourism and its several microforms, and cultural theory. The results showed the types of processed products such as urutan celeng metunu (smoked), urutan celeng medendeng (dried in the sun), the urutan celeng mekukus (steamed), and “Urutan Celeng” (just finished processing). Processing techniques that can be done to develop culinary tourism are related to the preparation of ingredients, processing of ingredients, and serving of food to be able to create new variations and good quality products for tourists to enjoy.